VISUALISASI OBJEK WISATA BUKITTINGGI DALAM SENI LUKIS CORAK SURREALIS - OSVI SYNTIA RAHMA DHANI, Drs. Suib Awrus, M.Pd, Dra. Jupriani, M.Sn (Universitas Negeri Padang, 2015)
This work aims to preserve the cultural and handicraft production in order to continue to exist back Galogandang society whose existence is decreased by the development of a functional form of the pot as cooking utensils into decorative objects. Pot decorated with ornaments sticking interesting, to captivate the public and able to penetrate the national and even international markets. Cultivation method works with presmolding and slab technique begins with the preparation, elaboration, synthesis, realization of the concept, the result of the product, until presented to the public through exhibitions.Kata Kunci: Belanga ,Galogandang, Payakumbuh, Kriya Keramik, Pengembangan & Dekorasi